MANAKAH PRIORITAS SEKTOR PENGEMBANGAN WAKAF DI INDONESIA? - AAM SLAMET RUSYDIANA; SUDANA SUDANA; LINA MARLINA (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2019)
In order to create a comprehensive policy, waqf institutions should determine the view of waqif(someone whotakes waqf ) related to which sector should be the priority of Indonesian waqf development in the future.This research would determine the preference of waqif related to the Indonesian waqf development in thefuture. This research used Analytic Network Process (ANP) method which was developed by Thomas L.Saaty to identify priority rank of waqf development. Based on the analysis result, it could be seen that themost prioritize of Indonesian waqf development was on the education sector. Waqif tended to trust waqfinstitution which have been actively involved in the education sector. It showed that education sector wasthe most important sector in Indonesia. Beside education, the second important ranked sector was the healthsector.Beside waqf development sector, analysis result found that priority of Indonesian development waqfwas more to the cash waqf. It showed that the cash waqf was viewed to be more important to be developedin Indonesia because the waqf property was liquid (in cash money).